Generalized power pompeiu type inequalities for local fractional integrals with applications to ostrowski's inequality - Erden, Samet; Sarikaya, Mehmet Zeki; Dragomir, Silvestru Sever; Erden, Samet (Isik University, 2019)
We establish some generalizations of power Pompeiu’s inequality for local fractional integral. Afterwards, these results gave some new generalized Ostrowski type inequalities. Finally, some applications of these inequalities for generalized special means are obtained. © 2021 Elsevier B.V., All rights reserved.
Keywords: Fractal Space; Local Fractional Integral; Ostrowski's Inequality; Pompeiu's Mean Value Theorem; Special Means